Sense and Manner of WASH and Their Coalition With Disease and Nutritional Status of Under-five Children in Rural Bangladesh: A Cross-Sectional Study - Kuddus, Mohammad Abdul; Sunny, Atiqur Rahman; Sazzad, Sharif Ahmed; Hossain, Monayem; Rahman, Mizanur; Mithun, Mahmudul Hasan; Hasan, Sayed Eqramul; Ahmed, Khandaker Jafor; Zandonadi, Renata Puppin; Han, Heesup; Ariza-Montes, Antonio; Vega-Muñoz, Alejandro; et al. (Frontiers in Public Health, 2022)
This study aimed to assess the knowledge and practice of caregivers and its relationship to the disease and nutritional status of children under five years of age in rural areas of Sylhet, Bangladesh. A total of 110 households with at least a child aged 6 to 59 months were selected by simple random method from ten rural communities of three Upazila of Sylhet from September 2019 to February 2020. Descriptive statistics were used to assess the "Water access, Sanitation, and Hygiene" (WASH) knowledge and practice, and multivariate chi-square analyses were performed to assess associations among diseases and nutritional status with WASH following a structured questionnaire. The study found a significant association of WASH with childhood disease and nutritional status, and 65% of children were found to be in a diseased state and 35% of children were found to be in a disease-free state within the last six months. The findings sketched that mother with poor WASH knowledge and practice was at greater risk for disease outbreaks, disease frequency, and duration. The highest incidence of diarrhea was 17% in children aged 12 to 23 months. A significant effect of WASH was also found in children's nutrition status, which was reflected in the ratio of stunted, underweight, and wasted children. Integrated convergent work focusing on providing clean water within the household, stopping open defecation, promoting handwashing, behavior change, and poverty alleviation is needed to improve the situation. Health, nutrition, and livelihood programs should be uninterrupted, and mothers or caregivers should be encouraged to participate in these programs.